Eyes Towards the Horizon: Structure-From-Motion Photogrammetry Enhances Understanding of Ship Petroglyphs from Rapa Nui (Easter Island) - Kühlem, Annette; Hartl-Reiter, Christian; Hey, Neka Atan Hey Atan; Pakarati, Singa (Waka Kuaka, 2019)
In this paper we present two petroglyphs of western sailing ships that were recently discovered on Rapa Nui (Easter Island). The far-reaching social ramifications of the arrival of the first Europeans have been discussed in a number of papers, but these newly found images allow for further insight into the effect their arrival had on the Rapanui population. Using structure-from-motion (SfM) macro photogrammetry we created detailed 3D images of the petroglyphs. This helped identify a hitherto unrecognised sense of accuracy and attention to detail employed in the depiction of a European ship by Rapanui artists. Their interest in the construction of European sailing ships, and reproductions thereof, are best understood in the context of the island’s isolation and the lost traditions of building ocean-going canoes.